The Effect of Capital Adequacy Ratio (CAR), Operating Expenses and Operating Income (BOPO), and Net Core Operating Margin (NCOM) on Financial Sustainability Ratio (FSR) in Islamic Banking in Indonesia for the 2017-2021 Period - Dwi Gusvita Anggraini; Nur Ahmadi Bi Rahmani; Muhammad Ikhsan Harahap (LPPM UIKA Bogor, 2023)
This study aims to determine the effect of the Capital Adequacy Ratio (CAR), Operating Expenses and Operating Income (BOPO), and Net Core Operating Margin (NCOM) on the Financial Sustainability Ratio (FSR) partially and simultaneously. This study used a quantitative approach. The type of data used is secondary data obtained from the annual financial statements published on the official website of each Sharia Commercial Bank for the 2017-2021 period. The sample in this study amounted to 10 Sharia Commercial Banks in Indonesia selected by purposive sampling method. The data analysis techniques used are descriptive statistical analysis, classical assumption tests, hypothesis tests, and multiple linear regression tests with the help of SPSS software. The results showed that the Capital Adequacy Ratio (CAR) had a partial positive and insignificant effect on the Financial Sustainability Ratio (FSR). In part, BOPO has a negative and significant effect on the Financial Sustainability Ratio (FSR). Partially, the Net Core Operating Margin (NCOM) has a positive and significant effect on the Financial Sustainability Ratio (FSR). Simultaneously, the variables Capital Adequacy Ratio (CAR), Operating Cost and Operating Income (BOPO), and Net Core Operating Margin (NCOM) have a significant effect on the Financial Sustainability Ratio (FSR) and the value of the coefficient of determination (R²) of 0.608 or 60.8%.